2023
DOI: 10.1002/ece3.9897
|View full text |Cite|
|
Sign up to set email alerts
|

Comparing ant morphology measurements from microscope and online AntWeb.org 2D z‐stacked images

Abstract: Unprecedented technological advances in digitization and the steadily expanding open-access digital repositories are yielding new opportunities to quickly and efficiently measure morphological traits without transportation and advanced/expensive microscope machinery. A prime example is the AntWeb.org database, which allows

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In the recent article by Báthori et al ( 2023 ), the authors would like to update the caption of Figure 1 as shown below:…”
mentioning
confidence: 99%
“…In the recent article by Báthori et al ( 2023 ), the authors would like to update the caption of Figure 1 as shown below:…”
mentioning
confidence: 99%